Ciproxifan, a Histamine h3 receptor antagonist as a potential therapeutic agent in Alzheimer's disease / Siti Murnirah Jaafar - Jaafar, Siti Murnirah (2015)
A Histamine H3 receptor antagonist, ciproxifan has been shown to enhance the release of neurotransmitters which play an important role in cognitive process. It is widely documented that extracellular deposition of ~-amyloidpeptide (A~) plays a causal role in the pathogenesis -of AD. However, the role of ciproxifan on A~ has not been well documented. The present study was aimed to investigate the ability of ciproxifan to inhibit BACE-l activity and to determine the neuroprotective effect of ciproxifan on A~ in vitro. Furthermore, the effect of ciproxifan on the AD related biomarkers was also investigated using APP(Sw) transgenic mice of AD model. The BACE-l inhibition activity was carried out using BACE-l assay kit while the SK-N-SH cells were induced with AP25-35 prior to the treatment with ciproxifan and then cell viability as well as ROS assay also was determined. For in vivo study, ciproxifan was administrated to the mice by intraperitoneal injection (i.p) for 15 days with two selective doses (1 and 3 mg/kg) and spatial learning and memory behaviour were assessed using radial arm maze (RAM). Brain tissues were collected to measure acetylcholine (ACh), acetylcholinesterase (AChE), nitric oxide (NO), lipid peroxidation (LPO), antioxidant activities, cyclooxygenase (COX) and proinflammatory cytokines assay while plasma were collected to measure an antiinflammatory cytokine TGF-I p. The results for in vitro study demonstrated that ciproxifan weakly inhibited BACE-I activity with IC50BAcE 500 11g/m1 and showed neuroprotective effect by increasing the cell viability and inhibited the production of ROS and these effects were comparable with positive control u-tocopherol.Meanwhile, ciproxifan significantly reduced time taken of the mouse to consume all five baits, working memory error and reference memory error in RAM. Ciproxifan did not show any alteration on the level of both ABI-40 and A~142 in APP transgenic mice.Ciproxifan also elevated the level of ACh while reduced AChE activity and showed anti-oxidant properties by reducing NO and LPG levels as well as enhancing the level of antioxidants (catalase, aSH and GPx). Moreover, the results of neuroinflammatory analysis showed that ciproxifan reduced both COX-I and COX-2 activities, decreased the level of pro-inflammatory cytokines IL-I (1, IL-I ~ and IL-6 and increased the level of anti-inflammatory cytokine TGF-I~. In conclusion, the present study suggests that ciproxifan possessed neuroprotective effect against A~ and could protect the SK-NSH cells from Ajl-induced toxicity by preventing the cell death through the inhibition of oxidative stress. However, protective effects of ciproxifan probably were not through the inhibition of BACE-lactivity and the reduction of Ap level but by other mechanism. The ameliorative effect of ciproxifan on memory deficit of APP transgenic mice may be mediated through improving cholinergic, antioxidant and antiinflammatory activities. This present study may provide some scientific evidences of ciproxifan through various mechanisms as a promising agent for the treatment of AD